artikel Zakat sebagai Instrumen Hukum dalam Mendukung Tujuan Pembangunan Berkelanjutan (SDGs) di Pedesaan - falyastaqiyunis, muhammad (Maliki Interdisciplinary Journal, 2025)
Zakat is not only a religious obligation but also a legal and social instrument with great potential to support sustainable development, especially in rural areas. With a strong legal foundation through Law Number 23 of 2011, zakat can be directed to address various rural development challenges, such as poverty, social inequality, and limited access to basic services. This article explores the strategic role of zakat in supporting the achievement of the Sustainable Development Goals (SDGs) in rural areas, as well as the challenges and strategies to strengthen its management.